Blended cement hydration assessment by thermogravimetric analysis and isothermal calorimetry - Meziani Meriem; Chelouah Nasser; Amiri Ouali; Leklou Nordine (MATEC Web of Conferences, 2018)
In the present study, the hydration of Portland cement pastes containing 5%, 10%, 15% and 20% tuff, limestone filler and granodiorite was investigated by thermogravimetric analysis coupled with differential scanning calorimetry and microcalorimetry isotherm. The monitoring of the hydration kinetics by thermogravimetric analysis made it possible to quantify the quantity of water combined with the cement (nonevaporable water) and the degree of hydration. By coupling this technique to the differential scanning calorimetry, it was also possible to measure the energy absorbed or released by the material during its decomposition. The results showed that the non-evaporable water content and the degree of hydration of the mixtures containing various mineral admixtures were relatively lower with respect to the reference mixture when as the content of mineral admixture increased. The effect of the evolution of the hydration process on the mechanical properties of mortars was also monitored. The relative variation of the compressive strength to that of the flexural strength was evaluated at 7, 28 and 90 days. Results showed that all the mixtures have a greater contribution in flexion than in compression.